Perubahan Iklim Dalam Konteks Sistem Produksi Dan Pengembangan Kopi Di Indonesia - Syakir, M.; Surmaini, E. (Badan Penelitian dan Pengembangan Pertanian, 2017)
Coffee is one of the Indonesian largest export commodities and has a strategic role in the economy of nearly two million farmers’ livelihood. The potency of Indonesia’s coffee export is quite high because of its preferred taste, however the trend of national coffee production is only 1-2% per year. On the other hand, the impacts of climate change also threaten the achievement of increased production targets. This paper reviews the impact climate change on coffee production and the adaptation strategies. The main coffee producing regions in Indonesia are Aceh, North Sumatera, South Sumatera, Lampung, Bengkulu, East Java and South Sulawesi Provinces. Most of these regions are vulnerable to climate change. The increasing of extreme climate events such as drought due to El Niño causes a decline in national coffee production to 10%. On the contrary, the longer wet season due to La Niña caused the decreased coffee production to 80%. Indirect impacts due to rising temperatures are increased incidence of coffee borer and leaf rust disease which can lead to a 50% decline on coffee production. Due to rising temperatures, the projected coffee production areas are projected to shift to higher elevations. Numerous adaptive technologies have been intoduced, however adaptive capacaity of farmers are still low. This condition is exacerbated by the limited access of most farmers to climate information, markets, technology, farming credits, and climate risk management information. To overcome the problem, policy makers, stakeholders and farmers have to accelerate the adaptation practices since the climate change has occurred and will continue to happen.Keywords: Coffee, climate change, production, adaptation Top of Form AbstrakKopi merupakan salah satu komoditas ekspor yang berperan strategis dalam perekonomian hampir dua juta rumah petani di Indonesia. Potensi ekspor kopi Indonesia cukup tinggi karena cita rasanya yang disukai, namun tren peningkatan produksi kopi nasional hanya 1-2% per tahun. Di sisi lain, dampak perubahan iklim juga mengancam tercapainya target peningkatan produksi. Makalah ini merupakan tinjauan dampak perubahan iklim terhadap produksi kopi dan strategi adaptasinya di Indonesia. Daerah penghasil utama kopi seperti Aceh, Sumatera Utara, Sumatera Selatan, Lampung, Bengkulu, Jawa Timur dan Sulawesi Selatan rentan terhadap dampak perubahan iklim. Meningkatnya kejadian iklim ekstrim seperti kekeringan akibat El Niño mengakibatkan penurunan produksi kopi 10%. Sebaliknya, musim hujan yang panjang akibat La Niña menurunkan produksi kopi hingga 80%. Dampak tidak langsung perubahan iklim adalah meningkatnya serangan hama penggerek buah kopi dan penyakit karat daun yang menyebabkan penurunan produksi sekitar 50%. Akibat kenaikan suhu, sentra produksi kopi diproyeksikan akan berpindah ke wilayah dengan elevasi yang lebih tinggi. Berbagai teknologi adaptasi telah dihasilkan, namun tingkat adaptasi petani kopi umumnya masih rendah. Kondisi ini diperparah oleh terbatasnya akses sebagian besar petani terhadap informasi iklim, pasar, teknologi, kredit usaha tani, dan informasi pengelolaan risiko iklim. Untuk mengatasi masalah tersebut, pengambil kebijakan, stakeholder, dan petani harus mengakselerasi upaya adaptasi karena perubahan iklim telah terjadi dan akan terus berlangsung.Kata kunci: Kopi, perubahan iklim, produksi, adaptasi